2012
DOI: 10.1016/j.bpj.2012.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Weak Interactions Govern the Viscosity of Concentrated Antibody Solutions: High-Throughput Analysis Using the Diffusion Interaction Parameter

Abstract: Weak protein-protein interactions are thought to modulate the viscoelastic properties of concentrated antibody solutions. Predicting the viscoelastic behavior of concentrated antibodies from their dilute solution behavior is of significant interest and remains a challenge. Here, we show that the diffusion interaction parameter (k(D)), a component of the osmotic second virial coefficient (B(2)) that is amenable to high-throughput measurement in dilute solutions, correlates well with the viscosity of concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
325
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(353 citation statements)
references
References 34 publications
(62 reference statements)
19
325
0
Order By: Relevance
“…5,51 This effect can be attributed to the antibody network formation at high protein concentration, which affects the packing volume fraction of the antibody and ultimately results in an increase in solution viscosity. 10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity. 52 Similar trends in viscosity in response to changes in solution conditions that we describe here for mAb-C have been reported for other IgG1 mAbs, where the extent of viscosity increased in a concentration-dependent manner with increasing ionic strength 11,18,30,53,54 and solution pH, 11,55 related to elevated levels of protein RSA due to charge shielding effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,51 This effect can be attributed to the antibody network formation at high protein concentration, which affects the packing volume fraction of the antibody and ultimately results in an increase in solution viscosity. 10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity. 52 Similar trends in viscosity in response to changes in solution conditions that we describe here for mAb-C have been reported for other IgG1 mAbs, where the extent of viscosity increased in a concentration-dependent manner with increasing ionic strength 11,18,30,53,54 and solution pH, 11,55 related to elevated levels of protein RSA due to charge shielding effects.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The RSA of mAbs presents various pharmaceutical challenges, including the formation of protein aggregation precursors that can lead to the irreversible formation of oligomers. 8,9 In addition, the RSA of mAbs gives rise to a network of associated higher-order species that can affect the viscoelastic properties of the solution, 10 resulting in increased viscosity, [5][6][7]11 solution turbidity, 12 and, under certain conditions, even phase transitions. 13 The increase in solution viscosity also imposes manufacturing challenges including high back-pressure and clogging of membranes, 2 as well as elevated levels of shear stress during pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al 38 suggested the following general guideline: Antibodies with B 22 greater than 2£10 ¡5 mL mol per gm 2 have solution viscosities lower than 20 cP at 150 mg per mL, provided B 22 and viscosity measurements are performed in the same formulation. 38 In a separate study, Connolly et al 39 40 In the data from Binabaji et al, mAbs that met the B 22 criterion of Saito et al had low solution viscosities at 150 mg per mL. However, Binabaji et al also reported that B 22 is insufficient to predict solution viscosities when mAb concentrations rise above 200 mg per mL.…”
Section: Theoretical Foundations and Experimentally Measurable Quantimentioning
confidence: 98%
“…5 At such high protein concentrations, due to increases in molecular crowding and decreases in intermolecular distances between molecules, the extent of specific and non-specific protein-protein interactions driven by exposed charged and apolar regions on the protein surface increase. [6][7][8] Independent of whether a protein is in vivo or in vitro (e.g., a purified protein drug candidate stored in a vial), molecular crowding causes protein solutions to deviate from ideality, thereby affecting macromolecular interactions and potentially protein conformation. 9 Identification of the interfaces that mediate protein-protein interactions can open new avenues for drug targeting and discovery, and guide protein engineers in the development of macromolecule candidates that are more stable and easier to administer.…”
Section: Introductionmentioning
confidence: 99%